Prevalence and Risk Factors of Sexual Dysfunction in Postpartum Australian Women - Khajehei, M.; Doherty, M.; Tilley, Peter; Sauer, K. (WILEY-BLACKWELL, 2015)
Introduction: Female sexual dysfunction is highly prevalent and reportedly has adverse impacts on quality of life. Although it is prevalent after childbirth, women rarely seek advice or treatment from health care professionals. Aim: The aim of this study was to assess the sexual functioning of Australian women during the first year after childbirth. Methods: Postpartum women who had given birth during the previous 12 months were invited to participate in this cross‐sectional study. A multidimensional online questionnaire was designed for this study. This questionnaire included a background section, the Female Sexual Function Index, the Patient Health Questionnaire (PHQ‐8), and the Relationship Assessment Scale. Responses from 325 women were analyzed. Results: Almost two‐thirds of women (64.3%) reported that they had experienced sexual dysfunction during the first year after childbirth, and almost three‐quarters reported they experienced sexual dissatisfaction (70.5 %). The most prevalent types of sexual dysfunction reported by the affected women were sexual desire disorder (81.2%), orgasmic problems (53.5%), and sexual arousal disorder (52.3%). The following were significant risk factors for sexual dysfunction: fortnightly or less frequent sexual activity, not being the initiator of sexual activity with a partner, late resumption of postnatal sexual activity (at 9 or more weeks), the first 5 months after childbirth, primiparity, depression, and relationship dissatisfaction. Conclusion: Sexual satisfaction is important for maintaining quality of life for postpartum women. Health care providers and postpartum women need to be encouraged to include sexual problems in their discussions.